PEMARAGRAFAN DALAM SURAT NIAGA BAHASA INDONESIA - Lidwina, Soeisniwati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2009)
In composing process of commercial letters, we need a clesr paragraph composition. According to my   knowledge, there  has not any research  about  Indonesian  Commercial  letters  paragraph  composition, yet. Therefore, I observe this issue. Some problems that may come up in my observation are the theme development of the letters, the connection between paragraphs, and the material s that have been used. The  goal  of  this  observation  is to  give  some  description  about Indonesian commercial letters paragraph composing,  that  is the development of the main ideas or the letters themes, harmonization of the connection between the sentences. This observation use thoroughly approaching method. The content of the trading mails was supposed to be one whole unit. After read all the commercial letters, I analyzed the elements that composed the mails, then I find the relation semantically, lexically, and grammatically. These observation files are in the grammar files form which related to commercial letters, including introduction letters, offerrequest, offerings, demands, and orders delivery from the private companies. All files werw collected by a content analysis, that is collecting all commercial  letters from the private companies and then the letters werw selected and sorted, make a note of the themes  development, the marker of the relation  between  sentences the marker of the relation between paragraphs semantically, lexically, and grammatically, including all kind of the commercial letters which was mentioned above. The observation  result shows that there  are tendencies  that the letter is paragraphs  content  by 2 and  3 paragrafs,  that  is opening  and closing paragraph, or opening, connector, and closing paragraph. Opening paragraphs always content by 1 paragraf, so that the cosing paragraphs, except on the 2 letters, that the closing paragraphs content by 2 paragrafs. The main ideas of each paragraphs content  by 1 idea. There are some tendencies that every paragraphs was made by  1 sentence, so the letter is idea is only a development of one single sentence. A commercial letter which   its   paragraphs   idea  was   developed   deductively,   the   relation between sentences  always  subordinative.  A commercial  letter which  its closing  paragraphs     content   by  2  sentences,   the  relation   between sentences always coordinative. The relation between paragraphs and sentences semantically, lexically, and grammatically always used by commercial  letters to create a harmonize  reading. There are tendencies that the relation between paragraphs always coordinative.  The semantic ways between the paragraphs which used by the letters are the relation of reason-result, the ways-the goal, the conditions- the result, additives (not the time additives), and time additives. There are some tendencies  that relation between  paragraphs that  have  been used  semantically  are the relation of reason-result.